Identifying the link between serum VEGF and KL-6 concentrations: a correlation analysis for idiopathic pulmonary fibrosis interstitial lung disease progression - Zhong, Bin; Luo, Shuixiang (Frontiers in Medicine, 2023)
Background Idiopathic pulmonary fibrosis interstitial lung disease (IPF-ILD) is a progressive lung disease characterized by excessive collagen deposition and fibrotic changes in the lungs. Identifying reliable serum markers that correlate with disease progression is crucial for diagnosis and prognosis. Objective This study aimed to explore the association between serum markers KL-6 and VEGF and IPF-ILD. Specifically, it assessed their correlation with PaO2, a measure of pulmonary gas function, to provide diagnostic and prognostic indicators. Methods Patients with IPF-ILD were included, and their serum levels of KL-6 and VEGF were measured. Correlations with fibrotic damage and PaO2 were analyzed using statistical methods. Results The analysis confirmed a positive correlation between the serum marker KL-6 and the degree of fibrotic damage in IPF-ILD. On the other hand, the serum marker VEGF was found to promote disease progression. In terms of correlation with PaO2, both KL-6 and VEGF demonstrated high sensitivity and specificity. Specifically, the correlation between KL-6 and PaO2 suggests that it can be used as a reliable indicator to assess the status of pulmonary oxygenation function in patients with ILD. The correlation between VEGF and PaO2 helps to understand its role in the progression of IPF-ILD and provides an important basis for predicting patient prognosis. Conclusion This study confirmed the correlation between KL-6 and VEGF with IPF-ILD and their association with PaO2. KL-6 and VEGF demonstrated high specificity and sensitivity in diagnosing, monitoring, and predicting prognosis in IPF-ILD. These findings contribute to our understanding of the disease and have clinical implications for diagnosis and prognostication.